The VASE LIFE RESPONSE OF TUBEROSE (Polianthes tuberosa L.) DUE TO GIVING GA3 AND SUGAR : VASE LIFE RESPONSE OF TUBEROSE (Polianthes tuberosa L.) DUE TO GIVING GA3 AND SUGAR - Wahyuni, Siti; Deden; Mubarak , Adham (Ann Publisher, 2024)
This study aims to determine the concentration of GA3 and the addition of sugar to the freshness of cut tuberose flowers. The research was conducted from May to June 2020, in Wano Village, Japara District, Kuningan Regency. The research method used was a Completely Randomized Factorial Design. The treatment consisted of 2 experimental factors, the concentration of GA3 with 4 treatment levels G0 (0 mg/l), G1 (50 mg/l), G2 (100 mg/l), and G3 (150 mg/l) with sugar concentration 4 treatment levels S0 (0 g/l), S1 (25 g/l), S2 (50 g/l), and S3 (75 g/l). Observations made were the decrease in fresh flower weight, number of blooming flowers, wilting period of flowers, total solution absorbed, and flower freshness period. The results showed that no interaction between GA3 and sugar treatments in all observation components. The GA3 treatment had no effect on all components of the observation, but the addition of sugar affected the reduction in fresh weight, wilting time of flowers, total solution absorbed and flower freshness. Treatment S3 (sugar 75 g/l) had the best results at a wilting period of 6.96 days, a total of 16.42 ml of absorbed solution, and a freshness period of 11.25 days.